2020
DOI: 10.1038/s41598-020-71561-2
|View full text |Cite
|
Sign up to set email alerts
|

Liver dysfunction is associated with poor prognosis in patients after immune checkpoint inhibitor therapy

Abstract: immune-related adverse events (irAes) are induced by immune checkpoint inhibitors (icis). Liver is one of the main target organs which irAEs occur and we investigated the influence of liver dysfunction on prognosis of patients after ICIs. From July 2014 to December 2018, 188 patients with diverse cancers who received icis (nivolumab or pembrolizumab) were enrolled. twenty-nine patients experienced liver dysfunction of any grades after ICIs. Progression-free survival (PFS) was significantly shorter in the liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In our study, patients with pAID had two times higher risk of developing both all-grade irAEs than controls, independently of known risk factors of irAEs, such as age, sex,27 28 the immunotherapy regimen29 and/or of disease status, such as the melanoma stage, the existence of hepatic or cerebral metastasis, the number of metastasis and the LDH values at baseline 30 31. Additionally, there were no difference between cases and controls for the body mass index values 32.…”
Section: Discussionmentioning
confidence: 46%
“…In our study, patients with pAID had two times higher risk of developing both all-grade irAEs than controls, independently of known risk factors of irAEs, such as age, sex,27 28 the immunotherapy regimen29 and/or of disease status, such as the melanoma stage, the existence of hepatic or cerebral metastasis, the number of metastasis and the LDH values at baseline 30 31. Additionally, there were no difference between cases and controls for the body mass index values 32.…”
Section: Discussionmentioning
confidence: 46%
“…In this study, patients who developed liver injury during atezo/beva treatments had a significantly shorter survival time than those who did not. Previous reports have shown that liver injuries are associated with poor prognosis in patients with cancer treated with ICI therapy [ 17 , 18 , 19 ]. Interestingly, the prognosis of patients with HCC with grade 1 or 2 liver injury during ICI treatments was also poor [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study had demonstrated the negative prognostic impact of liver dysfunction after ICI treatment. 21 However, liver dysfunction was rarely observed after nivolumab-based therapy in our patient population. The short duration of nivolumab use (median cycle = 3) and combination of chemotherapy ( n = 38) in the majority patients may preclude or reduce the occurrence of ICI-induced, immune-related, liver-associated adverse events.…”
Section: Discussionmentioning
confidence: 65%